Impact of COVID-19 Pandemic on Patients' Perceptions of Safety and Need for Elective Foot and Ankle Surgery in the United States. Issue 2 (4th June 2021) - Chan, Jimmy J.; Chen, Kevin K.; Choi, Peter; Rojas, Edward O.; Schipper, Oliver N.; Aiyer, Amiethab; de Cesar Netto, Cesar; Haleem, Amgad M.; Kadakia, Anish R.; Vulcano, Ettore
Background: With the development of the COVID-19 pandemic, elective foot and ankle surgeries were delayed throughout the United States to divert health care resources and limit exposure. Little is known about the impact of COVID-19 on patient's willingness to proceed with elective procedures once restrictions are lifted and factors contributing to such decision. Methods: Patients across 6 US orthopedic institutions who had their elective foot and ankle surgeries cancelled secondary to the pandemic were given a questionnaire. Specifically, patients were asked about their willingness to move forward with surgery once restrictions were lifted and if not why. Pain-level and pain medication use were also assessed. Univariate analysis was used to identify factors that contribute to patient's decisions. Results: A total of 150 patients participated in this study. Twenty-one (14%) opted not to proceed with surgery once restrictions were lifted. Forty-three percent (n = 9) listed concern for COVID infection as the reason; however, 14% of them would proceed if procedures were performed in surgery center. Twenty-nine (19% of the total cohort) patients had increased pain and 11% of patients were taking more pain meds because of the delay to their procedure. Patients who decided not to proceed with surgery reported pain reduction (3% vs 14%) and lower increase in pain medication used (5% vs 12%). Conclusion: COVID-19 has made a significant impact on the health care system. Delay of elective foot and ankle procedures impact patient quality of life and outcomes. Access to surgery centers may provide a partial solution during the pandemic Level of Evidence: Level III.